Fakt medialny - MAREK HENDRYKOWSKI (Images)
Fake news Marek Hendrykowskis analytical study concentrates on deep semantic structure and the social context of the news fabricated by media. Fake news is considered a functional expression of various prejudices, biases, stereotypes and emotions circulating in the common consciousness of contemporary society. When peoples emotions are intense, the impact of fictitious news is stronger and rational knowledge transmission is poorly explored. The critical re- actions of an individual viewer are seen as being particularly important to anticipatory regulation. The functional definition of “fake news” presented by the author provides a useful framework for organizing observations and interdisciplinary studies on this phenomenon.